(untitled) (Raparin Journal of Humanities (RJH), 2026)
We observe that cinema is in a constant state of change and development, both in terms of techniques and artistic form. It produces diverse films and outputs in terms of content and various complex models (dual propositions). Undoubtedly, all aspects and sections of film production have been influenced by the developments that occurred during the technological revolution. What draws attention is that viewers do not easily notice the efforts of the "unknown soldier" in the entire process—the person who strives with all their energy to produce a good film. This unknown soldier is the director, who is credited with the film’s success and bears the responsibility for its artistic and technical aspects. The director’s understanding, cultural level, intelligence, and artistic experience manifest their impact and signature in the film’s content. One of their primary duties is to translate the script, this written text, into a language of images, transforming static characters into vibrant individuals that come to life before our eyes, conveying the events and conflicts from the pages to the camera. The director bears the responsibility for these transformations, turning words, sentences, and scenes into imagination and visualization, which should be present in all films, regardless of their levels. Without imagination and visualization, there can be no event. Thus, the director is the backbone of producing a good and distinguished film, especially in Kurdish cinema, which has undergone many changes and developments in both artistic and technical aspects. However, in terms of creating images and imagination, this does not progress in parallel with the ongoing developments. Therefore, in this research, we aim to shed light on this important and sensitive topic.